Antiface / rosto imaginário: fabulações nas imagens geradas por softwares - Daneluz, Clarissa Rita (Universidade do Vale do Rio dos Sinos, 2021)
The work proposes fabulations in the face images generated by software. Along the way, some cases help us to fable: portraits of imaginary people and anti-face The objective is therefore to intuit conditions – audiovisual, media, technocultural – where face images become powers and variations of the human face updated by memory – collective and individual. The invitation to fabulation, imagination, fictionalization, is also an invitation to bring Henri Bergson, Walter Benjamin, and Aby Warburg closer to the thought. Around this we organize our empirical materials - collections of figures, montages - our descriptions, articulation essays between audiovisuals and communication, designed in contemporary technoculture. Our collection of “fabulous images” becomes like an album or portrait gallery.
Keywords: Comunicação audiovisual; Imagens de rosto; Fabulação; Software; Tecnocultura; Audiovisual communication; Face images; Fabulation; Technoculture; ACCNPQ::Ciências Sociais Aplicadas::Comunicação